DIGA-FAM Model (Differentiation Instruction and Game-Based Formative Assessment Model): Teacher Needs Analysis - Vivi Indriyani; Ary Ramadhan; Anisa Nurjanah; Trisna Helda (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
Formative assessment plays a crucial role in improving the quality of learning, but its practice in the classroom is often suboptimal due to limitations in media, methods, and suitability to student characteristics. This study aims to analyze teachers' needs in developing the DIGA-FAM Model (Game-Based Differentiated Learning and Formative Assessment Model) as an alternative formative assessment model that suits students' needs and characteristics. This study used a descriptive method with a survey approach through a questionnaire distributed to Indonesian language teachers in secondary schools. The questionnaire instrument focused on four aspects: teachers' needs for an assessment model, teachers' needs for assessment based on student characteristics, teachers' needs for effective feedback and student engagement, and teachers' needs related to digital-based assessment models. Data were analyzed descriptively and quantitatively to map the needs and obstacles faced by teachers. The results showed that teachers urgently need a formative assessment model that not only facilitates differentiated learning but also increases student motivation and engagement through a game-based approach. Furthermore, the integration of digital assessment is considered crucial to facilitate the implementation and continuous monitoring of student learning progress. These findings form an important basis for the development of the DIGA-FAM Model as an innovative solution that can address teachers' needs while supporting an effective and enjoyable learning process.